Navigation and meteorological data collected during the Tara Pacific Expedition 2016-2018 - Guillaume Bourdin; Fabien Lombard; Emmanuel Boss; G Gorsky; Clémentine Moulin; Guillaume Iwankow; Julie Poulain; Sarah Romac; Sylvain Agostini; Bernard Banaigs; Emilie Boissin; Chris Bowler; et al. (PANGAEA, 2022)
The Tara Pacific expedition (2016-2018) sampled coral ecosystems around 32 islands in the Pacific Ocean, and sampled the surface of oceanic waters at 249 locations, resulting in the collection of nearly 58,000 samples. The expedition was designed to systematically study corals, fish, plankton, and seawater, and included the collection of samples for advanced biogeochemical, molecular, and imaging analysis. Here we provide the continuous dataset originating from navigation and meteorological instruments acquiring continuously during the full course of the campaign.